A COMBINED FTIR AND TPD STUDY ON THE BULK AND SURFACE DEHYDROXYLATION AND DECARBONATION OF SYNTHETIC GOETHITE - Boily J.F.; Szanyi J.; Felmy A.R. (My University, 2006)
The thermal dehydroxylation of a goethite-carbonate solid solution was studied with combined Fourier-transform infrared (FTIR)-Temperature programmed desorption (TPD) experiments. The TPD data revealed dehydroxylation peaks involving the intrinsic dehydroxylation of goethite at 560 K and a low temperature peak at 485 K which was shown to be associated to the release of non-stoichiometric water from the goethite bulk and surface. The FTIR and the TPD data of goethite in the absence of adsorbed carbonate species revealed the presence of adventitious carbonate mostly sequestered in the goethite bulk. The release of carbonate was however not only related to the dehydration of goethite but also from the crystallization of hematite at temperatures exceeding 600 K. The relative abundance of surface hydroxyls was shown to change systematically upon goethite dehydroxylation with a preferential stripping of singly-coordinated {single bond}OH sites followed by a dramatic change in the dominance of the different surface hydroxyls upon the formation of hematite. ? 2006.
Keywords: CARBONATE; CRYSTALLIZATION; DEHYDROXYLATION; FTIR SPECTROSCOPY; GOETHITE; SOLID SOLUTION